2016
DOI: 10.1155/2016/6105142
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Granuloma in Odontogenic Cyst: An Enigmatic Lesion

Abstract: Cholesterol granuloma (CG) is the outcome of the foreign body type of response to the accumulation of cholesterol crystals and is frequently present in conjunction with chronic middle ear diseases. Recently, cases of CG in jaws have been reported, but still, very few cases have been found of CG in dental literature. This article presents three rare cases of CG in the wall of odontogenic cysts emphasizing on its possible role in expansion of the associated lesion and bone erosion. It also lays stress on the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…The presence of foreign body reaction with accumulation of cholesterol clefts involving macrophages and foreign body giant cells constituted the main feature ( Figure 1(d) ). The persistence of these cells may be the major source of cholesterol that is released by the destroyed membranes of these cells in chronic lesions [ 1 , 2 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of foreign body reaction with accumulation of cholesterol clefts involving macrophages and foreign body giant cells constituted the main feature ( Figure 1(d) ). The persistence of these cells may be the major source of cholesterol that is released by the destroyed membranes of these cells in chronic lesions [ 1 , 2 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of maxillary sinus CG is still uncertain and its occurrence has been reported secondarily to bleeding, inadequate lymphatic drainage, poor ventilation, trauma, surgery, sinusitis, and odontogenic lesions [ 3 , 7 , 11 , 12 ]. It has been suggested that inflamed odontogenic lesions could show a foreign body reaction to the cholesterol crystals in their capsule, and as the capsule expanded it may possibly reach the maxillary sinus [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is not uncommon that a cholesterol granuloma will form within a dentigerous cyst [ 3 ] or similar structure in response to an inflammatory insult, such as a tooth root infection; however, in this instance, the incomplete lining of the lesion was not obtained during the biopsy. The lack of both previous insults, mechanical or microbiological, marks this case as unusual, as nearly all previously reported cases had indications of prior trauma or infection associated with the region in which the cholesterol granuloma formed.…”
Section: Case Presentationmentioning
confidence: 99%
“…Lipophagy was reported in lipid-laden macrophages (foam macrophages) (59, 60) and in memory CD8 T cells (61) in odontogenic cyst (62)(63)(64). IL-12 is important in CD8 T-cell clonal expansion in addition to the generation of memory CD8 T cells (65).…”
Section: Radicular Cystmentioning
confidence: 99%
“…IL-12 is important in CD8 T-cell clonal expansion in addition to the generation of memory CD8 T cells (65), which in turn stimulate lipophagy (Figure 8B). Lipophagy was reported in lipid-laden macrophages (foam macrophages) (59,60) in odontogenic cyst (63) and in memory CD8 T cells (61). Additionally, IL-12A inhibits VEGF and MMP-9 reducing angiogenesis (66).…”
Section: Radicular Cystmentioning
confidence: 99%